DIAGNOSIS KESULITAN BELAJAR BANGUN RUANG SISI LENGKUNG DI KELAS XI SMKN 1 PERCUT SEI TUAN - Dhita Thivani Linch Hutabarat; Ainul Marhamah Hasibuan; Azizah Yusra Amaliyah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine what causes students' learning difficulties in studying mathematics on curved side space geometry in class XI of SMKN 1 Percut Sei Tuan. This type of research is a descriptive type of research with a qualitative approach. The population in this study were all students of SMKN 1 Percut Sei Tuan. The sample in this study was 32 students of class XI of SMKN 1 Percut Sei Tuan. Data collection used questionnaires, interviews, and tests on curved side space geometry. Based on the results of the questionnaire instrument, there were 4 forms of learning difficulties including; students who felt they had difficulty because they did not understand with a percentage of 39.06%, students who felt they were not careful in doing the test with a percentage of 42.96, students who felt the test was difficult with a percentage of 13.28%, and students who did not know anything about curved side space geometry with a percentage of 4.68%. Then based on the results of the test instrument, there were criteria that caused students' learning difficulties including; students who experienced conceptual errors with a percentage of 12.5%, students who experienced errors in using arithmetic operations with a percentage of 9.68%, students who completed the test with an imperfect algorithm with a percentage of 8.43%, and students who completed the test carelessly with a percentage of 8.43%.